Synthesis, Characterization, and Hydrogen Isotope Storage Properties of Zr1-xTixCo and Zr1-xHfxCo Alloys (x = 0.1, 0.2). (4th July 2021) - Monea, Bogdan Florian; Ionete, Eusebiu Ilarian; Ducu, Catalin; Spiridon, Stefan Ionut; Moga, Sorin; Han, Xingbo; Liu, Wei
Abstract: In the present study, the effect of Hf and Ti substitution of Zr in the ZrCo alloy, used for hydrogen isotope storage, has been investigated in order to ascertain the improvement of the anti-disproportionation property of ZrCo hydrides. The ultimate goal of the investigation is to develop a safe and economically viable solution for the long-term storage of deuterium and tritium. The intermetallic compounds Zrl-x Tix Co and Zrl-x Hfx Co (x = 0.1, 0.2) were prepared and their suitability for hydrogen isotope storage, protium (H) and deuterium (D), was investigated. The alloys were synthesized by arc melting under a controlled argon atmosphere and characterized by scanning electron microscope and X-ray diffraction analysis. The hydrogen isotope storage behavior of these alloys was probed by loading and unloading protium and deuterium. We present the pressure, composition, and temperature measurements for desorption, together with the thermodynamic parameters (enthalpy and entropy) of these alloys. The experimental results show that Ti and Hf substitution in the ZrCo alloys is suitable for fast delivery of hydrogen isotopes, even after their long-term storage.